System Telemetry for Mobile Devices Using the GPS Neo-6M and DHT11 Modules A Case Study by IMEI Team - Cholilurrohmana Cholilurrohmana; Indah Sulistiyowati; Arief Wicaksana (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2023)
Telemetry systems are used during Formula One (F1) and Shell Eco Marathon (SEM) races to monitor car conditions and performance during the race. This telemetry system is designed to monitor the performance of the car in real time by obtaining data about speed, steering room temperature, and other parameters. The purpose of making this tool is to be able to strategize during a good and efficient race. In this research on telemetry system development, several sensors and electronic devices are used to monitor car performance. This telemetry system consists of several sensors installed on the car, such as the U-blox Neo 6m GPS sensor and the DHT 11 sensor. These sensors collect data and transmit it to the control unit, which then sends the data to the server. The method used in this research includes several stages, namely telemetry system development, trials and testing, and data analysis. The main result of this research is the development of a telemetry system that can monitor the performance of electric cars in real-time. This telemetry system can provide useful information for the driver on the track and the team at the track. In addition, the results of this research also show that the telemetry system developed can produce accurate and reliable data. An electric car telemetry system can be a very useful tool for electric car users and manufacturers in improving the efficiency and performance of electric cars. In this study, the development of the telemetry system has successfully produced a tool that can monitor the performance of electric cars in real time and provide useful information for users and electric car manufacturers. It is hoped that the results of this research can help in developing more efficient and environmentally friendly electric car technology in the future